Оценка человеческого капитала промышленного предприятия в условиях экономических кризисов - Руссиян, Е.А.; Ляшок, Н.Ю. (Економіка промисловості, 2012)
Проведен анализ подходов к оценке человеческого капитала промышленных предприятий. Выделены ограничения существующих подходов для их применения в кризисных условиях. Предложен подход к оценке человеческого капитала промышленных предприятий в условиях экономических кризисов на основе учета принципов затратного подхода и параметров человека, что направлено на повышение объективности оценки человеческого капитала в кризисных условиях.
Ключевые слова: оценка, человеческий капитал, кризисные условия, затратный подход, параметры человека, промышленное предприятие. Проведено аналіз підходів до оцінки людського капіталу промислових підприємств. Виділено обмеження існуючих підходів для їх застосування в кризових умовах. Запропоновано підхід до оцінки людського капіталу промислових підприємств в умовах економічних криз на основі врахування принципів витратного підходу і параметрів людини, що спрямоване на підвищення об'єктивності оцінки людського капіталу в кризових умовах.
Ключові слова: оцінка, людський капітал, кризові умови, витратний підхід, параметри людини, промислове підприємство. The paper analyzes the approaches to assessing human capital at industrial enterprises. The restrictions in the application of existing approaches in crisis situations are identified. The approach is offered that can be used for assessing human capital of industrial enterprises under the economic crises. It takes into account the principles of the cost approach and human parameters and makes the assessment of human capital more objective under crises situations. The advantages of this approach also include the possibility of economic assessment of the appropriateness of investments in human capital of the company in terms of its value.
The scientific and methodical approach to the assessment of human capital developed and described in the paper allows increasing the efficiency of industrial enterprises activity based on human capital development in conditions of resources crises. Assessment of human capital forms the basis for choosing the strategy and decision-making in human capital management of industrial enterprises in conditions of the economic crisis. The approach to the assessment of human capital at industrial enterprises also forms the basis for knowledge management development as a motivational factor.
Keywords: assessment, human capital, crisis situations, cost approach, human parameters, industrial enterprise.